Evaluation of Tweed’s Facial Triangle among Students in Lagos, Nigeria - Adebisi. Ajisafe, Olawande; Ogunbiyi. Ogunbanjo, Babatunde; Olubukola. Adegbite, Kikelomo; Oyapero, Afolabi (Orthodontic Journal of Nepal, 2020)
Introduction: The advent of cephalometric analysis has aided orthodontic diagnostic procedures, while the Tweed’s facial triangle which is a type of cephalometric analysis has complemented routine orthodontic treatment planning. This aim of this study was to evaluate Tweed’s facial triangle among a selected Nigerian population with normal occlusion. Materials & Method: A sample of 100 subjects, selected by multistage sampling from three schools in Ikeja local government, Lagos State had lateral cephalometric radiographs taken. The final sample analysis of the radiographs was 84. The error of the cephalometric method was assessed using the intra-class correlation co-efficient. The Tweed’s facial triangle was analyzed on the cephalometric radiographs and comparison between this Nigerian population and Tweed’s Caucasian cohort was carried out. Result: Out of the 84 subjects, 41(48.8%) were males and 43(51.2%) females. This study reported mean values of 23.26° ± 4.78° for FMA, 54.08° ± 5.11° for FMIA and 103.47° ± 6.26° for IMPA. Females had higher FMIA and IMPA values compared to males which was statistically significant for FMIA. The FMA was higher in males with a statistically significant difference between genders. The results suggest increased proclination of lower incisors in this Nigerian population compared to Tweed’s Caucasian population. Conclusion: The mean values for Tweed’s facial triangle in this Nigerian population were significantly different from that obtained by Tweed. Orthodontists should aim at achieving these values when analyzing cephalometric radiographs using Tweed’s facial triangle in Nigerians. This will further aid proper diagnosis, treatment planning with or without extractions and planning of retention after orthodontic treatment.